Systems of Formation in Foucaults Archaeology: Incursion to Sub-Levels of Discourse (Global Journal of Medical Research, 2022)
Since the first undertakings carried out in its name in the 1960s, discourse analysis has shown itself to be a remarkably broad and diverse investigative field. In its french tendency, we could possibly relate the hybridity of this field to the achievements of Michel Foucault, whose discursive theory owes its elaboration to the interest addressed by the philosopher towards debates brought about by encounters and confrontations that took place in the field of social and human sciences during the 20th century. However, Foucault#x2019;s text The Archeology of Knowledge, which can be considered as a founding work regarding the French school of discourse analysis, constitutes its theoretical place positively apart from linguistic analysis and from the textual dimension of discourse. Therefore, to approximate to linguists the theoretical developments Foucault carries out in the Archeology of Knowledge, it seems convenient to recover some of the discussions which might have served as a condition for this text to be presented the way we know it today. Considering the limits of space we have, we decided to analyze the degree and the way of use in Foucault's discursive theory of the structural analysis method as L#xE9;vi-Strauss envisioned it for the work of ethnological science in the middle of the last century, considering moreover the effects produced by the notion of structure he recommended in the way historians thought of social duration. Concerning the methodological approach, we use a set of texts related to the debate established between history and anthropology in France in the last century which we suppose have served as a condition of possibility for the production of the Archeology of Knowledge. Confronting these texts with Foucault's work, we explore the existing intertextual relationships between the Archeology and this material whose previous existence seems to have enabled its appearance. In this direction, we adjust the condition of possibility to which we refer, reducing its scope to what we have decided to take strictly as a textual condition of possibility #x2013; a category we assume as theoretical support in our analytical work. The results show us that certain traits of structuralist reason seem to have been transferred to a theoretical aspect of Archeology defined as system of formation #x2013; an underlayer in which multiple elements of social reality establish reciprocal relationships whose complex systematicity serves as a condition of existence to the elements of discourse.
Keywords: structuralism the archeology of knowledge discourse analysis michelfoucault l#xE9; vi-strauss